The Role of Peaceful Means to Solve Political Crisis: The Case of Qatar Blockade - Al-Saaadi, Mansoor Ahmed (Journal of Economic, Administrative and Legal Sciences, 2021)
The current research investigates the role of amicable means in resolving the political crisis in case of Qatar blockade. The key objective of the research is to review and evaluate the role of international and regional efforts in resolving the political crisis in case of Qatar blockade. The descriptive historical methodology was used in the research. Results showed that amicable means are the most suitable means of resolving the regional crisis and conflicts in GCC. It was found that regional efforts are better than international efforts in resolving crisis. Based on that, it is recommended that GCC states should cooperate to resolve their conflicts and crisis.
Keywords: amicable means; political crises; regional disputes; international mediation; blockade of Qatar